2021
DOI: 10.1002/nag.3246
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of microcracking behaviors in brittle rock using polygonal grain‐based distinct method

Abstract: The failure process in brittle rocks is an important topic in rock mechanics, whose good understanding assists in predicting the strength and deformation characteristics of rocks. Because it is difficult to directly observe microcracks in laboratory tests, a numerical model is a useful tool for investigating microcracking behaviors. However, the mechanism of microcrack evolution is still unclear at the grain scale considering the microscopic heterogeneities. This paper proposes a polygonal universal distinct e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Numerical simulation was conducted, because it is powerful in revealing the microscopic failure behaviour of materials (Chen et al, 2019;Wang et al, 2021). In addition, numerical simulation was able to reproduce the tensile failure process of the cement paste.…”
Section: Numerical Simulation Schemementioning
confidence: 99%
“…Numerical simulation was conducted, because it is powerful in revealing the microscopic failure behaviour of materials (Chen et al, 2019;Wang et al, 2021). In addition, numerical simulation was able to reproduce the tensile failure process of the cement paste.…”
Section: Numerical Simulation Schemementioning
confidence: 99%
“…Various approaches inspired by the Bonded‐Particle‐Model (Potyondy & Cundall, 2004) have been proposed in order to represent in the same numerical framework an initially elastic medium which can progressively damage and fracture (Asadi et al., 2012; Hazzard & Young, 2000; Kim & Buttlar, 2009; Park & Min, 2015; Potyondy, 2007; Wanne & Young, 2008). A recent trend in rock mechanics is to enrich the traditional circular/spherical representation of grains by considering an initial assembly of polygonal bodies (Saksala & Jabareen, 2019; Z. Wang et al., 2021). This geometry allows to consider samples without any initial porosity, and to represent more accurately the nucleation and the development of fractures and microcracks and the associated dilatancy.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown how DEM simulations can be used as a powerful tool to study the characteristics of AE events in rocks (and concrete) before, during, and after failure. [23][24][25][26][27] The complex and somewhat stochastic post-failure response and its correlation with the pre-failure characteristics evade the current rock-mechanics frameworks. This is the domain where artificial intelligence (AI) and machine learning (ML), and particularly DL methods 28 can provide powerful tools for capturing temporal correlations in AE and stress-strain data to predict the post-failure responses.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is possible to track the energy release in the form of AE when a cohesive bond breaks. Recent studies have shown how DEM simulations can be used as a powerful tool to study the characteristics of AE events in rocks (and concrete) before, during, and after failure 23–27 …”
Section: Introductionmentioning
confidence: 99%